Pulmonary physiology - Levitzky, Michael G. (McGraw-Hill Education Medical/Lange, 2013)
For more than three decades, Michael Levitzky has provided medical students and residents with a solid background in the areas of pulmonary physiology essential for a thorough understanding of clinical medicine. This 8th teaches you how and why the human respiratory system works--in a style and presentation that makes it easy to absorb and integrate with your knowledge of other body systems.